Natural History of Perianal Fistulising Lesions in Patients With Elderly-onset Crohn's Disease: A Population-based Study. (22nd October 2019) - Danielou, Marie; Sarter, Hélène; Pariente, Benjamin; Fumery, Mathurin; Ley, Delphine; Mamona, Christel; Barthoulot, Maël; Charpentier, Cloé; Siproudhis, Laurent; Savoye, Guillaume; Gower-Rousseau, Corinne; ,
Abstract: Introduction: Most studies of elderly-onset Crohn's disease [CD; diagnosed in patients aged 60 or over] have described a mild course. However, data on the natural history of perianal fistulising CD [pfCD] in this population are scarce. In a population-based cohort study, we described the prevalence, natural history, and treatment of pfCD in patients with elderly-onset CD vs patients with paediatric-onset CD. Method: All patients diagnosed with CD at or after the age of 60 between 1988 and 2006, were included [ n = 372]. Logistic regression, Cox models, and a nested case-control method were used to identify factors associated with pfCD. Results: A total of 34 elderly patients [9% of the 372] had pfCD at diagnosis. After a median follow-up of 6 years (interquartile range [IQR]: 3; 10), 59 patients [16%] had pfCD; the same prevalence [16%] was observed in paediatric-onset patients. At last follow-up, anal incontinence was more frequent in elderly patients with pfCD than in elderly patients without pfCD [22% vs 4%, respectively; p < 10 –4 ]. Rectal CD at diagnosis was associated with pfCD: hazard ratio (95% confidence interval [CI] = 2.8 [1.6–5.0]). Although 37% of the patients received immunosuppressants and 17% received anti-tumour necrosis factor agents, 24% [14 out of 59] had a definitive stoma at last follow-up. Conclusion: During the first 6 years of disease, the prevalence of pfCD was similar in elderly and paediatric patients. Rectal involvement was associated with the appearance of pfCD in elderly-onset patients. Around a quarter of patients with elderly-onset CD will have a stoma. Our results suggest that treatment with biologics should be evaluated in these patients.